Peranan Karbohidrat dalam Perspektif Al-Qur’an - Setiawan, Maulana; Wiratama, Ichsan; Sulaeman, Alif (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2022)
Carbohydrates are compounds consisting of the elements carbon, hydrogen and oxygen, carbohydrates have an important role for life for humans, animals and plants. Carbohydrates and their functions have been described in several verses of the Qur'an.. The perspective of the Qur'an on science, especially on carbohydrates, is sometimes less known to most people that carbohydrates are important to study. The abundance of food on this earth, makes humans less aware and negligent about the importance of the benefits of carbohydrates. The purpose of this study is to find out about the role of carbohydrates in the Qur'an, encourage the development of science in the perspective of the Qur'an, increase faith and gratitude for all God's gifts. The research method in this article uses literature studies, writing techniques to collect data and information by reviewing related journals and books. The result of writing this article is that carbohydrates have an important role, source and impact according to the view of the Qur'an. The conclusion obtained is that the role of carbohydrates has been explained in the Qur'an in the letter (Qur'an: 4, Al-Maidah: 88), the source of carbohydrates (Al-An'am: 95, Yasin: 33, Al-Baqarah: 22, An-nahl; 11, An-Nahl: 68-69), and its impact (Al-A'raf: 31, Al-Maidah: 87).